Strategies of Refugee Children in Response to Ethnic Categorization and Social Exclusion in Konya - Fuat Güllüpınar; Gamze Kaçar Tunç (Journal of Economy Culture and Society, 2024)
In this paper, we focus on how refugee children from Syria, Afghanistan, Iraq, and Sudan resettled in Konya, Turkey, use coping strategies in response to the ethnic categorization and exclusion policies of the local population. Employing ethnographic methodology combined with grounded theory, we conducted participant observations, as well as in–depth interviews with 65 refugee children. The family members of the children, as well as the local population, were also within the scope of the study. Furthermore, we conducted extensive interviews and observations in two different religious secondary schools attended by refugees. We aimed to understand their local experiences and intergroup relations by expanding the field. As a result, we observed that these children resisted societal pressure by developing various coping strategies such as emphasizing Muslim identity, attending schools as spaces for socializing, choosing to speak Turkish, standing with the strong, and building shared enjoyment or joining existing ones. These findings show that the refugee children do not passively submit to the conditions they find themselves in and do not simply embrace the impositions of power as they are.